Efficacy and Safety of Bedside Removal of Tunnelled Hemodialysis Catheter by Noninterventional Nephrologists among Adult Patients in the King Abdulaziz University Hospital Hemodialysis Centre in Jeddah: A Retrospective Cohort Study - Abdullah Kashgary; Razan A. Almuhyawi; Reem R. Alhijri; Aseel M. Ba Durayq; Wed B. Alnagrani; Arwa J. Alharbi; Hamidah M. Al Khalaf; Haya S. Obaid; Ahmed Zaky Fadel; Mostafa Abdelsalam (International Journal of Nephrology)
This study aimed to assess the efficacy and safety of bedside removal of tunnelled hemodialysis catheter (TDC) by noninterventional nephrologists among adult patients. It is a retrospective study that involved 53 patients from March 2020 to February 2022 at the King Abdulaziz University Hospital (KAUH) Hemodialysis Centre in Jeddah, Saudi Arabia. Of the 53 participants, 60.4% were male and 40.6% female, and their mean age was 50.94 ± 18.89 years. The most common comorbidities were hypertension (HTN) in 47 (88.7%), diabetes mellitus (DM) in 24 (45.3%), and DM and HTN together in 23 (43.4%) patients. The most common site of TDC removal was the right internal jugular vein (77.4%). In 84.9% of the cases, the TDC was removed as an inpatient procedure, and in the majority of the cases (64.2%), the TDC was removed by a noninterventional nephrologist. The most common reasons for TDC removal were sepsis or clinical concerns for infection (64.2%) and TDC not needed (20.8%) due to recovery of the renal function or access maturation. Most patients (96.2%) suffered no complications; only one of 34 (%) patients with catheter removal by a noninterventional nephrologist had bleeding, which required more observation and monitoring before discharge on the same day. Our study revealed that the bedside TDC removal was well tolerated with a minimal complication rate.